(untitled) (Medical Forum Monthly, 2026)
Objective: To study the impact of intermittent self-catheterization (ISC), performed by the patient after trained by a specialist nurse, on reducing the recurrence of female urethral stricture disease after their urethral dilation. Study Design: Randomized controlled trial (RCT) studyPlace and Duration of Study: This study was conducted at the Urology Department of Shaikh Zayed Hospital, Lahore, Pakistan from December 2024 to May 2025. Methods: A total of 132 female patients (aged 31-60 years) were recruited and randomized into two groups. Intervention group (n=66) performed intermittent self-catheterization (ISC) twice a week at home, whereas the control group (n=66) did not perform ISC at home at all. Both the groups were followed up by the researcher after every 15 days of recruitment for 12 consecutive weeks. Urethral stricture recurrence was assessed on every follow up visit by passing a 12Fr Nelton and catheterization failure was labelled as urethral stricture recurrence. Results: Intervention group showed statistically significant (p=0.005) reduction in the recurrence 07/27 (25.93%) in comparison with 20/27 (70.07 %) recurrence in control group. The main bulk of recurrences 18/27 (66.67%) were reported on the very first follow up within first 15 days, irrespective of their group allocation. Conclusion: After urethral dilatation intermittent self-catheterization (ISC) performed by patients themselves after adequate training by a specialist nurse significantly reduces the stricture recurrence.